Analysis of the potential for retrieving cloud optical depth and particle size of thin ice clouds using infrared thermal radiometry in an arctic environment - Blanchard, Yann (HAL CCSD, 2011)
An important goal, within the context of improving climate change modelling, is to enhance our understanding of aerosols and their radiative effects (notably their indirect impact as cloud condensation nuclei). The cloud optical depth (COD) and average ice particle size of thin ice clouds (TICs) are two key parameters whose variations could strongly influence radiative effects and climate in the Arctic environment. Our objective was to assess the potential of using multi-band thermal radiance measurements of zenith sky radiance for retrieving COD and effective particle diameter (Deff) of TICs in the Arctic. We analyzed and quantified the sensitivity of thermal radiance on many parameters, such as COD, Deff, water vapor content, cloud bottom altitude and thickness, size distribution and shape. Using the sensitivity of IRT to COD and Deff, the developed retrieval technique is validated in comparison with retrievals from LIDAR and RADAR. Retrievals were applied to ground-based thermal infrared data acquired for 100 TICs at the high-Arctic PEARL observatory in Eureka, Nunavut, Canada and were validated using AHSRL LIDAR and MMCR RADAR data. The results of the retrieval method were used to successfully extract COD up to values of 3 and to separate TICs into two types : TIC1 characterized by small crystals (Deff< 30 microns) and TIC2 by large ice crystals (Deff> 30 microns, up to 300 microns). Inversions were performed across two polar winters. At the end of this research, we proposed different alternatives to apply our methodology in the Arctic. Dans le contexte actuel de changements climatiques, il est crucial d'approfondir nos connaissances des nuages de glace fins (TIC) et de leurs paramètres intensifs et extensifs. Les TICs peuvent avoir pour effet de refroidir ou de réchauffer le climat, en fonction de leurs paramètres météorologiques et microphysiques. Ainsi, l'épaisseur optique (COD) et la taille des particules sont essentiels pour pouvoir simuler les nuages de glace dans les modèles climatiques. ...